Friction properties of moulding thermoplastics - Pouzada, A. S. (2006)
During the ejection phase of the injection moulding cycle the parts are mechanically forced to separate from the moulding surfaces, this aspect being more relevant with deep cores. The design of the ejection system depends on factors such as the draft angles, the surface finish, and the properties of the moulding material at the ejection temperature and the dimensioning of actuation devices (e.g., hydraulic or pneumatic cylinders). Knowledge of the friction properties of the mating metal and plastics surfaces is important to optimize the ejection system. The coefficient of friction at the ejection stage depends on the surface texture of the core and the temperature at ejection. This paper reviews recent research on the static coefficient of friction in moulding conditions. It also reviews results obtained with a prototype apparatus that reproduces the conditions occurring during the ejection phase.